A Target‐Directed Chemo‐Photothermal System Based on Transferrin and Copolymer‐Modified MoS2 Nanoplates with pH‐Activated Drug Release. Issue 47 (2nd August 2017) - Zhang, Aitang; Li, Aihua; Tian, Wenxue; Li, Zichao; Wei, Chen; Sun, Yong; Zhao, Wei; Liu, Mengli; Liu, Jingquan
Abstract: Molybdenum disulfide (MoS2 ) nanosheets have attracted significant attention due to their photothermal properties, but the poor solubility and colloidal stability limited their further application in biomedical field. Here, we report a targeted photothermal controllable nanocarrier consisting of MoS2 nanosheets modified with block copolymer P(OEG‐A)‐ b ‐P(VBA‐ co ‐KH570) and targeting ligand transferrin. P(OEG‐A)‐ b ‐P(VBA‐ co ‐KH570) is synthesized by RAFT polymerization and utilized not only to improve the solubility of MoS2 nanosheets but also efficiently load the anti‐cancer drug doxorubicin (DOX) through an acid‐cleavable Schiff base linker. Thiol‐functionalized transferrin (Tf‐SH) is anchored onto the surface of MoS2 nanosheets by the formation of disulfide bonds, which could further enhance the cellular uptake of DOX and MoS2 to HepG2 cells for high‐efficiency synergetic therapy. The drug release experiments exhibited the minimal release of DOX at room temperature and neutral pH, and the maximal drug release of 53 % at acidic tumor pH and hyperthermia condition after 48 h. In addition, the DOX‐loaded, Tf‐SH and P(OEG‐A)‐ b ‐P(VBA‐ co ‐KH570) modified MoS2 (DOX‐POVK‐MoS2 ‐Tf) showed better a therapeutic effect than DOX‐POVK‐MoS2 and POVK‐MoS2, probably owing to the combined effects of target‐directed uptake, acid‐triggered drug release, and NIR induced localized heating, which suggest the designed MoS2 nanocarriers are promising for applications in multi‐modal cancer therapy. Abstract : A target‐directed chemo‐photothermal therapy system with pH‐activated drug release behavior is prepared based on MoS2 nanoplates modified with transferrin and copolymer P(OEG‐A)‐ b ‐P(VBA‐ co ‐KH570). The as‐prepared DOX‐POVK‐MoS2 ‐Tf nanocomposites exhibit well a therapeutic effect to HepG2 cells owing to the combined effects of target‐directed uptake, acid‐triggered drug release and NIR‐induced localized heating, which suggest the designed MoS2 nanocarriers are promising for active‐targeting chemo‐photothermal synergetic therapy.